2002
DOI: 10.1007/bf02867938
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effect of monosodium glutamate (MSG) administration on the activity of xanthine oxidase, superoxide dismutase and catalase in hepatic tissue of adult male mice

Abstract: Subcutaneous administration of monosodium glutamate (MSG), to normal adult male mice, for six consecutive days at dose levels of 4 and 8 mg/g body weight, significantly increased the level of free radical initiating enzyme, xanthine oxidase, whereas the activity of free radical scavenging enzymes, like catalase and superoxide dismutase was significantly decreased in hepatic tissue. These observations suggested that ingestion of MSG at dose level of 4 mg/g body weight and above, induced oxidative stress in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…These will result in a decrease of cell pH that will affect and damage the lysosome membrane, resulting in the breakdown of lysosomes and the release of enzymes into the cytoplasm. 32 On the other hand, a decrease in ATP production will also decrease Na + K + ATPase function. This situation will lead to an accumulation of intracellular Na+ and increases the cellular osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…These will result in a decrease of cell pH that will affect and damage the lysosome membrane, resulting in the breakdown of lysosomes and the release of enzymes into the cytoplasm. 32 On the other hand, a decrease in ATP production will also decrease Na + K + ATPase function. This situation will lead to an accumulation of intracellular Na+ and increases the cellular osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…45 Both GSH and SOD are abundant in the liver and they participate in cell protection against ROS and against cancer development. 43,46 SOD catalyzes the breakdown of the superoxide anion into oxygen and hydrogen peroxide and GSH detoxifies hydrogen peroxide in presence of GSH peroxidase. 47 Sun et al 48 observed an inhibition in SOD activity in EAC-bearing animals that may be attributed to loss of mitochondria and loss of Mn SOD activity in EAC cells, resulting in a lowering in total hepatic SOD activity.…”
Section: Discussionmentioning
confidence: 99%
“…SOD are a class of closely related enzymes that catalyze the breakdown of the superoxide anion into oxygen and hydrogen peroxide (Zelko et al, 2002). The amount of SOD is organ specific and it is abundant in hepatic tissue (Singh and Ahluwalia, 2002). CAT is a key component of the antioxidant defense system.…”
Section: Discussionmentioning
confidence: 99%